2008
DOI: 10.1111/j.1574-6976.2008.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of polynitroaromatic compounds: the bacterial nitroreductases

Abstract: Most nitroaromatic compounds are toxic and mutagenic for living organisms, but some microorganisms have developed oxidative or reductive pathways to degrade or transform these compounds. Reductive pathways are based either on the reduction of the aromatic ring by hydride additions or on the reduction of the nitro groups to hydroxylamino and/or amino derivatives. Bacterial nitroreductases are flavoenzymes that catalyze the NAD(P)H-dependent reduction of the nitro groups on nitroaromatic and nitroheterocyclic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
344
1
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(391 citation statements)
references
References 261 publications
4
344
1
11
Order By: Relevance
“…Previous studies have found that Enterococcus is often enriched in the nitroaromatic nitrobenzene-reducing biocathode communities, and the relative abundance can reach 38.4% or 74.7% (Wang et al, 2011). This was consistent with the fact that Enterococcus and Pseudomonas species own nitroaromaticsreducing ability (Rafii et al, 2003;Roldan et al, 2008). These results indicated that the microbial community structure with applied electrical stimulation was obviously different from that of the open circuit biofilm.…”
Section: Potential Function Of Dominant Generasupporting
confidence: 78%
See 2 more Smart Citations
“…Previous studies have found that Enterococcus is often enriched in the nitroaromatic nitrobenzene-reducing biocathode communities, and the relative abundance can reach 38.4% or 74.7% (Wang et al, 2011). This was consistent with the fact that Enterococcus and Pseudomonas species own nitroaromaticsreducing ability (Rafii et al, 2003;Roldan et al, 2008). These results indicated that the microbial community structure with applied electrical stimulation was obviously different from that of the open circuit biofilm.…”
Section: Potential Function Of Dominant Generasupporting
confidence: 78%
“…A recent study has found that Citrobacter was obviously enriched by 29.24% in a glucose-fed azo dye-reducing biocathode community (Sun et al, 2016). Relatively low abundances of Desulfovibrio (from 1.63 to 2.04% in the electrode biofilms), Salmonella (from 0.14 to 1.17% in the electrode biofilms) and Clostridium (4.35% in the open circuit biofilm) were also detected, which have been reported to carry out nitroaromatics reduction by nitroreductase (Roldan et al, 2008;Spain, 1995). Collectively, cathode potential regulation strategy stimulated the microbial electrode respiration activity, and enriched different electroactive respectively.…”
Section: Potential Function Of Dominant Generamentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that both the 11 BC_1619 and BC_3024 enzymes followed a ping pong bi bi reaction mechanism . Taken together, the 12 two novel proteins from B. cereus were classified as oxygen-insensitive nitroreductases, based on the 13 following characteristics: reduce nitro-groups to hydroxylamine derivatives in presence of oxygen; 14 follow a ping pong bi bi mechanism; require NADH or NADPH as cofactors; are homodimers; contain 15 a FMN prosthetic group; and are strongly inhibited by dicoumarol [47,48,49]. 16 In order to decide on names that most closely described the two novel proteins, both homology 17 searching and biochemical characterisations were used to rename the B. cereus enzymes.…”
mentioning
confidence: 99%
“…The toxic effects are related to the electrophilic character of these derivatives, while the mutagenic effects are mainly due to the formation of hydroxylamine adducts resulting from esterification with the nucleic acid guanine. Additionally, some nitroaromatic compounds are intrinsically toxic and function as uncouplers of oxidative phosphorylation, inhibiting the generation of the proton motive force required for ATP synthesis (Roldán et al, 2008).…”
Section: Introductionmentioning
confidence: 99%